2019
DOI: 10.2169/internalmedicine.2475-18
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with MPO-ANCA-positive IgA Nephropathy Diagnosed with the Clinical Onset of Macrohematuria

Abstract: A 21-year-old woman presented with renal dysfunction during macrohematuria. A kidney biopsy revealed IgA nephropathy with a small percentage of crescent formation and macrohematuria-associated tubular injury. Macrohematuria-associated acute kidney injury could explain her renal dysfunction. However, she was seropositive for myeloperoxidase (MPO)-anti-neutrophil cytoplasmic antibody (ANCA) and showed fibrin deposition around one arteriole. Corticosteroids and mycophenolate mofetil were administered as for ANCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are great differences in clinical manifestations and prognoses between IgAN and AAV, and the coexistence of IgAN and ANCA positivity was very uncommon. There are only case reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and 2 small case control studies [20,21] that reported some of the features of IgAN patients with ANCA positivity. This study explored the clinicopathological and prognostic features of IgAN patients with ANCA positivity in a large consecutive cohort with long time follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…There are great differences in clinical manifestations and prognoses between IgAN and AAV, and the coexistence of IgAN and ANCA positivity was very uncommon. There are only case reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and 2 small case control studies [20,21] that reported some of the features of IgAN patients with ANCA positivity. This study explored the clinicopathological and prognostic features of IgAN patients with ANCA positivity in a large consecutive cohort with long time follow-up.…”
Section: Introductionmentioning
confidence: 99%